What is Global Health Equity? A Proposed Definition. Issue 1 (4th July 2022) - August, Ella; Tadesse, Lia; O'Neill, Marie S.; Eisenberg, Joseph N. S.; Wong, Rex; Kolars, Joseph C.; Bekele, Abebe
The term "global health equity" has become more visible in recent years, yet we were unable to find a formal definition of the term. Our Viewpoint addresses this gap by offering a discussion of this need and proposing a definition. We define global health equity as mutually beneficial and power-balanced partnerships and processes leading to equitable human and environmental health outcomes (which we refer to as "products") on a global scale. Equitable partnerships actively work against racism and supremacy. Such partnerships foster processes with these same dynamics; for example, sharing lead authorship responsibilities with meaningful roles for host country researchers to frame relevant questions and to provide context and interpretation for the research findings. Equitable products, such as access to technology and tailored delivery of interventions effective in the specific context, are the fruits of these partnerships and processes.